Multidisciplinary Management of Breast Cancer in Pregnant - Josef Maria Seno Adjie; Anna Sofyana; Yudianto Budi Saroyo; Jen Marisi Marbun; Intje Sheilla Dahlan (Indonesian Socety of Obstetrics and Gynecology, 2026)
Abstract Objective: The incidence of breast cancer in pregnant women is noted to be 1 in 3000 – 10000 women. This case report aims to examine the management of breast cancer in pregnant patients, taking into account holistic factors and the importance of teamwork among various professional disciplines. Methods: A Case Report Case Presentation : In this case report, a 37-year-old woman, G3P2, 23 weeks gestational ag with breast cancer during pregnancy. Biopsy results showed stage II invasive papillary carcinoma of the breast, which progressed to an advanced stage. The patient and her husband were convinced in a family meeting to continue the pregnancy with coordinated multidisciplinary team. After undergoing conservative management, a cesarean section was performed at 31 weeks of gestation . The patient gave birth to a baby boy weighing 1355 grams with an Apgar Score of 6/8. Currently, the patient is undergoing outpatient care in the hematology oncology department and the baby is undergoing outpatient care with the pediatrics department. Discussion:Clinical experience and patient values are essential considerations in making appropriate management decisions. The management dilemma in this case required a holistic approach, facilitated by a social obstetrics and gynecology consultant. Clinical assessment indicated that early termination of pregnancy would not necessarily improve maternal prognosis, supporting the decision to continue conservative management. The multidisciplinary team conducted counselling through family meetings, ensuring that both patient and family were actively involved in the decision-making process. Therefore, obstetricians and gynecologists, particularly those engaged in social obstetrics and gynecology, play a crucial role as facilitators to achieve mutual agreement that reflects the expectations of all parties. Conclusion: This case demonstrates the importance of understanding a holistic approach and multidisciplinary team collaboration in decision-making for patients with breast cancer during pregnancy. Keywords: Holistic, Breast Cancer, Pregnancy